Skrining fitokimia dan uji aktivitas antioksidan ekstrak metanol daun salam (Syzygium polyanthum (Wight.) Walp.) dari Gampong Bunot, Pidie Jaya dengan metode DPPH - Nazirah, Nazirah; Nasution, Muhammad Amin; Ridwanto, Ridwanto; Nasution, Haris Munandar (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Antioxidants are compounds that can delay, slow down, or inhibit the oxidation reaction of food or medicine. Antioxidants include electron-donor compounds that work by donating an electron to compounds that are free radicals so that radical activity is inhibited. One of the plants that can be used as a source of natural antioxidants is salam leaf (Syzygium polyanthum (Wight.) Walp). Salam leaves contain secondary metabolite compounds, including alkaloids, tannins, saponins, steroids, triterpenoids, and flavonoids, which act as antioxidants. The study aimed to determine whether the methanol extract of salam leaves (Syzygium polyanthum (Wight.) Walp.), which grows in Gampong Bunot, Pidie Jaya, contains secondary metabolites and has activity as an antioxidant. This research was conducted experimentally, where the sample used was salam leaves. The stages of this research included the processing of plant materials, preparation of methanol extract of salam leaves, characterization examination, phytochemical screening, and antioxidant activity test of methanol extract of salam leaves using the DPPH method. Salam leaf extract was prepared by maceration method using methanol solvent obtained and concentrated with a rotary evaporator, then the phytochemical screening test and the antioxidant activity test of the methanol extract of salam leaves were carried out using the DPPH method (1,1 diphenyl-2-picrylhidrazil) at a wavelength of 516 nm and vitamin C as a comparison. Based on the results of the phytochemical screening test, there were differences in secondary metabolites in the methanol extract of salam leaves grown in Gampong Bunot, Pidie Jaya, including alkaloids, flavonoids, saponins, tannins, steroids, and glycosides. The results of the antioxidant activity test of the methanol extract of salam leaves obtained the IC value50 of 25.68 µg/ml and the IC value50 Vitamin C of 4.537 µg/ml in the second category is very strong.